2018
DOI: 10.1080/09537104.2018.1557619
|View full text |Cite
|
Sign up to set email alerts
|

Rapid testing of red blood cells, white blood cells and platelets in intensive care patients using the HemoScreen™ point-of-care analyzer

Abstract: Acute major bleeding is a condition that can be encountered in critically ill patients and may require rapid transfusions. To evaluate the need for packed red blood cells (RBCs) and platelets (PLTs), it is important to have rapid test results for RBC/hemoglobin and PLTs. Recently, PixCell Medical (Yokneam Ilit, Israel) introduced the HemoScreen™, an automated hematology analyzer. It is a point-of-care device that uses single sample cuvettes and image analysis of RBCs, PLTs and white blood cells (WBCs), perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
(31 reference statements)
0
11
0
1
Order By: Relevance
“…Over the entire measuring range, we found that the HemoScreen correlated very well for the routine samples in all five parameters to those generated by the Sysmex XN (Figures ). As seen by Larsson et al, 29 the HemoScreen, at low PLT counts, tend to slightly underestimate the counts compare with the Sysmex instrument (Figures 2B and 4B); however, this is of no clinical importance.…”
Section: Discussionmentioning
confidence: 57%
“…Over the entire measuring range, we found that the HemoScreen correlated very well for the routine samples in all five parameters to those generated by the Sysmex XN (Figures ). As seen by Larsson et al, 29 the HemoScreen, at low PLT counts, tend to slightly underestimate the counts compare with the Sysmex instrument (Figures 2B and 4B); however, this is of no clinical importance.…”
Section: Discussionmentioning
confidence: 57%
“…Las correlaciones de Deming entre el HemoScreen y el analizador de Sysmex XN: Leucocitos (Leucocitos HemoScreen™ = 1.061* Lecucoitos Sysmex -0.644; r = 0.995), eritrocitos (Eritrocitos HemoScreen™ = 0.998* Eritrocitos ysmex + 0.049; r = 0.993) y plaquetas (Plaquetas HemoScreen™ = 1.087* Plaquetas Sysmex -14.80; r = 0.994). El dispositivo HemoScreen™ produce resultados rápidos y exactos para evaluar las necesidades de transfusión de glóbulos rojos y de plaquetas 33 .…”
Section: Analizador Hematológico Automatizadounclassified
“…Currently, there has been the use of point-of-care hemoglobin (POC-Hb) for hemoglobin measurement. Many studies have reported the clinical use of POC-Hb in various settings, including blood donation [6][7][8] and anemia screening [7], hemoglobin monitoring during cardiac operation [9], and hemoglobin measurement in intensive care unit patients [10,11]. Hemoglobin is a protein in red blood cells and functions in oxygen delivery to the tissues.…”
Section: Introductionmentioning
confidence: 99%